2019
DOI: 10.1002/hed.25603
|View full text |Cite
|
Sign up to set email alerts
|

High metastatic node number, not extranodal extension, as a node‐related prognosticator in surgically treated patients with nodal metastatic salivary gland carcinoma

Abstract: Background The prognostic relevance of extranodal extension (ENE) for salivary gland carcinoma (SGC) remains unclear. The present study is undertaken to investigate the predictive significance of pathological nodal parameters in surgically treated patients with nodal metastatic SGC. Methods This multicenter cohort included 114 patients with pathologically proven node‐positive SGC between 2000 and 2014. Possible correlations of clinicopathological parameters and outcomes were examined. Results The median follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…A N2 or N3 stage was defined if there was a LN greater than 3 cm, and worse prognosis was predicted compared to a N0/N1 neck. However, after adjusting for the number of positive LNs, the LN size was no longer associated with OS; this finding was also reported by Aro et al 7 Contralateral neck metastasis constituted at least a N2c stage, but it was extremely rare in parotid MEC, and no N2c stage was noted in the current study and N2c stage occurred in only 2.6% of the 114 salivary gland cancer patients in a study by Hsieh et al 19 and 0.3% of 4520 salivary cancer patients in a study by Aro et al 7 As no rich lymphatic network existed between the left and right parotid glands, the real incidence of N2c in parotid cancer in the two studies was lower. This further validates the superiority of our proposed N stage.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A N2 or N3 stage was defined if there was a LN greater than 3 cm, and worse prognosis was predicted compared to a N0/N1 neck. However, after adjusting for the number of positive LNs, the LN size was no longer associated with OS; this finding was also reported by Aro et al 7 Contralateral neck metastasis constituted at least a N2c stage, but it was extremely rare in parotid MEC, and no N2c stage was noted in the current study and N2c stage occurred in only 2.6% of the 114 salivary gland cancer patients in a study by Hsieh et al 19 and 0.3% of 4520 salivary cancer patients in a study by Aro et al 7 As no rich lymphatic network existed between the left and right parotid glands, the real incidence of N2c in parotid cancer in the two studies was lower. This further validates the superiority of our proposed N stage.…”
Section: Discussionsupporting
confidence: 88%
“…Lee et al 18 enrolled 172 patients, and ENE occurred in 31.4% of patients and the presence of ENE was related to an additional 1.5‐fold risk of overall death, cancer‐caused death, and disease recurrence in multivariate analyses. However, plenty of evidence also supports the viewpoint that ENE does not demonstrate any influence on survival, but is correlated directly with PNI, LVI, neck stage, and metastatic LN burden; therefore, the inferior survival might be driven by these adverse pathologic features, not ENE 6,7,19 . Our finding also sustained this perspective, in that ENE was relatively uncommon and it did not pose additional compromise to OS, reflecting the rationality of our proposed N stage.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hong et al, in a cohort of 87 patients with high-grade salivary gland cancer, found that ENE independently affected only DFS. [15] Aro et al [17] and Hsieh et al [37] demonstrated that ENE did not have any impact on survival. It is worth mentioning, however, that a recent report did identify ENE as one of the most important prognostic predictors [18].…”
Section: Extra-nodal Extensionmentioning
confidence: 99%
“…However, this official stage is formulated according to head and neck squamous cell carcinoma, and there are apparent differences in biological features between head and neck squamous cell carcinoma and PGC [ 3 ]. There have been discussions concerning the rationality of the official N stage in PGC [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%